Plan de Comunicación Integral para el área de Operaciones de la empresa ICSSE, proyecto de EP PETROECUADOR, Quito, año 2014 - Ontaneda López, Diana Cristina (2014)
This dissertation project aims at creating a comprehensive communication plan in the area of operations ICSSE CIA. LTDA, to strengthen interpersonal relationships, information flow, knowledge transfer and communication in general and thus retain one of its major customers as is EP Petroecuador. For the development of this plan first study the problem to determine the factors that directly affect organizational communication .Moreover the relevant aspects of the business are spelled ICSSE exposed, then the theoretical framework is established, the that all concepts related to communication are specified. ICSSE situational analysis followed metologíco this a study is made by primary and secondary sources is then performed. with the results of the situational analysis and research, a SWOT matrix is made to consecutively make the presentation of the proposed communication plan. Finally conclusions and recommendations to assess the effectiveness of the project and key issues to consider in implementation were formulated.